Effect of Ti particles on microstructure and mechanical properties of Mg–9Al–1Zn based composite sheets - Xudong Chen; Jun Xu; Kaihong Zheng; Xintao Li; Tianguo Wang; Shengli Han; Yuehua Kang; Bo Feng; Hong Yang; Nan Zhou; Weiwen Zhang; Fusheng Pan (Journal of Materials Research and Technology, 2023)
It is a great challenge to simultaneously improve the strength and ductility of magnesium matrix composites (MMCs). In this work, AZ91 alloys reinforced with 1 wt%, 2 wt%, and 3 wt% Ti particles were produced using stir casting combined with ball milling process. The microstructure of the extruded composite sheets was analyzed by X-ray diffraction (XRD), scanning electron microscope (SEM), electron backscatter diffraction (EBSD). Transmission electron microscopy (TEM) was utilized to observe the structure of the Ti/Mg interface. The mechanical properties of the composite sheets were also investigated. The results show that the adding Ti particles, the texture strength decreased, and the growth of recrystallization grains was also restrained. Due to the interfacial reaction between Ti and Al, the formation of β-phase (Mg17Al12) was inhibited. The tensile test demonstrated that the Ti particles could significantly improve the mechanical properties of the AZ91 alloy sheets. Compared to AZ91 sheet, 2Ti/AZ91 composite sheet along extrusion direction (ED) showed the best comprehensive mechanical properties. The improvement in mechanical properties was mainly attributed to grain refinement, texture weakening, mismatched coefficient of thermal expansion (CTE), and work hardening.